PATRIOTISM - AN IMPORTANT FACTOR OF STABILITY AND DEVELOPMENT OF SOCIETY (Modern American Journal of Social Sciences and Humanities, 2026)
This article analyzes the moral and philosophical essence of patriotism, its role in human spirituality and societal development. It also highlights the features of patriotism as a moral principle, its significance in the formation of a person's worldview and spiritual maturity. Based on the scientific views of scientists on patriotism, the content of this concept, its aspects related to humanism, national identity, and universal values are considered. In the article, patriotism is interpreted not only as a feeling of love for the Motherland, but also as a high moral quality aimed at preserving its development, independence, and values.